004.3 Adolescent care-seeking behaviour after notification of positive sexually transmitted infection results. (13th September 2015) - Trent, M; Chung, S; Harris, B; Huettner, S; Butz, A; Gaydos, C
Abstract : Background: Adolescents with pelvic inflammatory disease [PID] are at risk for recurrent sexually transmitted infections [STI]. There is limited understanding of adolescent responses to notification of subsequent STI. The objective of this study was to examine care-seeking trends after notification. Methods: This study utilised data from 59 of 153 adolescents with PID enrolled in the Technology Enhanced Community Health Nursing [TECH-N] study with positive STI results at 1-month or 3-month study visits. Participants provided vaginal specimens for Neisseria gonorrhoeae [GC], Chlamydia trachomatis [CT], Trichomonas vaginalis [TV], and Mycoplasma genitalium [MG]. Participants were called with results and an outreach worker contacted hard-to-reach participants in the field. Participants were referred for free treatment in a youth-friendly clinic. TECH-N staff tracked treatment using the electronic health record and communication with the health department. Statistical analyses were performed to evaluate responsiveness to notification. Results: Mean age of participants with positive results was 18.1 (2.1) and 44% had a prior STI. At 1-month, positives were 26% CT; 5% GC; 37% TV; 53% MG. At 3 months, positives were 16% CT; 11% GC; 49% TV; 51% MG. All adolescents with positive results were contacted and 50% sought treatment. 60% of CT 0% of GC, 55% of MG, and 57% of TV positives did not seek treatment. 42% who were positive at 1 month remained positive at 3-months. Using GC/CT treatment as a reference, documented treatment rates for positive results were CT/GC (50%) versus MG (54%) at 1 month and TV (60%) and at 3-months were CT/GC (80%) versus MG (55%) and TV (17%). Despite the 3-month trend, differences did not reach statistical significance. Conclusion: Most adolescents who tested positive for STIs after PID were responsive to notification. However, many youth did not seek treatment despite the availability of free, confidential, and youth-friendly sexual health services. Disclosure of interest statement: This study was funded by the National Institute of Nursing Research, Grant # R01NR013507, PI: Trent).